Antimicrobial Activity Derivatives 2H-pirano[2,3-c]piridines against Pathogens of Intestinal Yersiniosis - Ivannik, V.Yu.; Torianyk, I.I.; Moiseienko, T.M.; Skliar, A.I.; Yeromenko, R.F.; Hnatiuk, V.V.; Podrigalo, L.V.; Nazaryan, R.S.; Mikhailenko, N.M.; Gargin, V.V. (Journal of Pharmacy and Nutrition Sciences, 2021)
Background: An important aspect in the treatment of patients with intestinal yersiniosis is the administration of effective antibiotic therapy. Performed research aimed to determine the spectrum and level of antimicrobial activity of 2H-pyrano[2,3- c]pyridine derivatives on the museum and clinical strains of gram-negative microorganisms Yersinia enterocolitica. Methodology: The object of the study was 28 synthetic derivatives of 2H-pyrano[2,3- c]pyridine. The compounds were studied according to their chemical structure. We used the method of serial dilutions in Muller-Hinton liquid nutrient medium with a museum’s and clinical strains of Y.enterocolitica. Results: Studies indicate the promise of further study of the properties of 2H- pyrono[2,3-c]pyridine to create an effective antimicrobial medicine. According to the results of studies on action of antimicrobial compounds synthesized on the basis of 2H-pyrano[2,3-с]pyridine derivatives, it was found that the MIC of compounds for all Y. enterocolitica strains was 100.0 μg/ml. The MBCC of most cultures of Yersinia (72.3 %) was 200.0 μg/ml. Compound 23 had a pronounced antiyersiniotic activity, the inhibitory effect of which was manifested at a concentration of 25.0 μg/ml. Retarding the growth of most Yersinia strains (95.3%) with a MIC of 50.0 μg/ml, the MIC of compounds ranged from 50.0 to 200.0 μg/ml. After statistical data processing, pyridine derivatives (compounds 23 and 35) were identified, possessing an effective bacteriostatic and bactericidal effect on Y. enterocolitica strains. Conclusions: The results of the research showed a high antimicrobial activity of 2H- pyrano[2,3-c]pyridine derivatives. The highest activity against Y. enterocolitica was found for 2-N2-arylimino-5-hydroxy-methyl-8-methyl-2H-pyrano[2,3-c]pyridine-3-N1- aricarboxamide derivatives.